2019
DOI: 10.19132/1807-8583201946.15-23
|View full text |Cite
|
Sign up to set email alerts
|

Whitehead, CD Projekt RED e desenvolvimento de jogos: entrevista com Marcin Blacha

Abstract: Entrevista com Marcin Blacha, designer de jogos e Diretor de Narrativa do estúdio CD Projekt RED sobre as conexões entre os estudos acadêmicos e o desenvolvimento de jogos. Blacha aborda a aproximação da Filosofia de Whitehead e o design de jogos, assim como temas referentes as singularidades dos jogos desenvolvidos fora do eixo anglófono.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Games Studies, we opted for a framework of multidisciplinary studies where intersections with Communication are found, but which differ from research in other disciplines by placing games and the activity of playing as a central theme and not just as mere examples (FRAGOSO; AMARO, 2018). Through Game Studies, we understand the challenge of studying games not only as objects, but as processes that only occur with the participation of players (AARSETH, 2001).…”
Section: /20mentioning
confidence: 99%
“…In Games Studies, we opted for a framework of multidisciplinary studies where intersections with Communication are found, but which differ from research in other disciplines by placing games and the activity of playing as a central theme and not just as mere examples (FRAGOSO; AMARO, 2018). Through Game Studies, we understand the challenge of studying games not only as objects, but as processes that only occur with the participation of players (AARSETH, 2001).…”
Section: /20mentioning
confidence: 99%